Evaluasi Sistem Kompensasi dalam Meningkatkan Kepuasan Kerja Karyawan - Mariah, Siti; Faisal, Muslim (Lembaga Pengembangan Kinerja Dosen, 2025)
The compensation system is one of the important aspects in human resource management that is designed to motivate, attract and retain employees. The purpose of this study is to evaluate the current compensation system in Chickenin Saozan with a focus on looking at the relationship between the compensation system and the level of employee job satisfaction. This study was conducted with a qualitative research approach and type, where the data collection method was in the form of observation, interviews and documentation. The study focused on evaluating the company's compensation system in Chickenin Saozan and the object of the study involved several aspects such as financial compensation, non-financial compensation and job satisfaction. The data analysis method in this study used a qualitative approach with a focus on data reduction, presentation and drawing conclusions. The results of the study showed that the compensation system and bonus system provided by the company have not been able to meet employee expectations. The compensation standard is still too far from employee expectations and has not met the standards in force in Indonesia, which is 10-15% lower than the industry standard, while the bonus system tends to be uniform without considering individual performance. Non-compliance with regulations, especially regarding the provision of THR which does not reach one full month's salary, also has an impact on decreasing employee motivation and job satisfaction.